2011
DOI: 10.1155/2011/896474
|View full text |Cite
|
Sign up to set email alerts
|

ER Stress and Iron Homeostasis: A New Frontier for the UPR

Abstract: The C282Y mutation of HFE accounts for the majority of cases of the iron overload disease Hereditary Hemochromatosis (HH). The conformational changes introduced by this mutation impair the HFE association with β 2-microglobulin (β 2m) and the cell surface expression of the protein: with two major consequences. From a functional perspective, the ability of HFE to bind to transferrin receptors 1 and 2 is lost in the C282Y mutant, thus affecting hepcidin regulation. Also due to the faulty assembly with β 2m, HFE-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 113 publications
(137 reference statements)
1
13
0
Order By: Relevance
“…This effect can be mediated by ischemic stimulation 12 but also by the action of hemoglobin degradation products including iron 13 . Previous studies revealed that CHOP mediates apoptosis after cerebral ischemia 14 .…”
Section: Discussionmentioning
confidence: 99%
“…This effect can be mediated by ischemic stimulation 12 but also by the action of hemoglobin degradation products including iron 13 . Previous studies revealed that CHOP mediates apoptosis after cerebral ischemia 14 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been shown that alterations in iron homeostasis can affect the fatty acid metabolism [21] and apolipoprotein B secretion [28], contributing to lipid metabolism abnormalities and intracellular lipid accumulation in the liver. Additionally, it has been demonstrated that aberrant iron metabolism contributes to insulin resistance [29], inflammation [30] and the induction of oxidative and endoplasmic reticulum stress [13,17], key events in the pathogenesis of NAFLD. Among these processes, the effect of aberrant iron metabolism on the progression of NAFLD to its advanced states, especially fibrogenesis [11,31,32], may be the most significant.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have indicated a tight interaction between lipid and one-carbon metabolism, the induction of oxidative and endoplasmic reticulum stress and hepatic iron homeostasis in the molecular pathogenesis of both alcoholic and nonalcoholic liver injury [16][17][18][19]. Importantly, it has been demonstrated that steatosis, inflammation and other NAFLD-related molecular abnormalities are attenuated as NAFLD progresses or after removal of the causative factor, while the peculiarities in iron-related metabolism are exacerbated [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…C/EBPa inhibits the expression of other members of C/EBP family, and CHOP exhausts this inhibition and enhances the expression of hepcidin [5,6]; we suspect that the up-regulated expression of hepcidin exacerbates apoptosis. Hepcidin regulates cellular iron efflux by inducing internalization of ferroportin-1 (Fpn1) [7].…”
Section: Introductionmentioning
confidence: 97%